Asymptotic methods in fluid mechanics survey and recent advances - Steinruck, Herbert (Wien New York Springer, 2010)
A survey of asymptotic methods in fluid mechanics and applications is given including high Reynolds number flows (interacting boundary layers, marginal separation, turbulence asymptotics) and low Reynolds number flows as an example of hybrid methods, waves as an example of exponential asymptotics and multiple scales methods in meteorology.
Keywords: Fluid mechanics -- Mathematics; Asymptotes; Electronic books